Volume 10 Number 2 2014
DOI: 10.18057/ijasc.2014.10.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Corrosion of Steel Plates Coupled With Titanium

Abstract: Over twenty six percent of the bridges in the United States are structurally deficient or functionally obsolete. Corrosion of steel used in structures like bridges and buildings is a problem that has gained increased interest and focused concern. Steel is often the metal that is preferred for use in such applications due to a synergism of ease of availability, acceptable mechanical properties and cost effectiveness. Through the years, titanium has grown in strength, stature and significance to be recognized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies have extensively explored the corrosion behavior of these composite plates in marine environments [11][12][13], focusing on aspects such as surface corrosion, electrochemical behavior, and long-term stability. Li et al investigated the performance of 316L stainless steel and A6 carbon steel composite plates under neutral salt spray tests, observing significant elemental overlap at the composite interface [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have extensively explored the corrosion behavior of these composite plates in marine environments [11][12][13], focusing on aspects such as surface corrosion, electrochemical behavior, and long-term stability. Li et al investigated the performance of 316L stainless steel and A6 carbon steel composite plates under neutral salt spray tests, observing significant elemental overlap at the composite interface [12].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al investigated the performance of 316L stainless steel and A6 carbon steel composite plates under neutral salt spray tests, observing significant elemental overlap at the composite interface [12]. Patnaik et al indicated that the coupling of titanium with steel accelerates the corrosion of steel due to titanium's more noble position in the electrochemical series [13]. Prolonged exposure led to accelerated corrosion along the interface of A6 carbon steel components, surpassing the corrosion rate of the carbon steel matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiencies affect the durability and even influence the safety of structure. Previous and current research mainly focuses on the effect of cracks to the capacity of structures [1]. Reasons causing these deficiencies may be different from bridge to bridge, but changes of vehicle load and loss of pre-stressing are the most common and critical reasons.…”
Section: Introductionmentioning
confidence: 99%